Geo-statistical methods to analyse changes in pre-Hispanic settlement patterns in the Río Ica catchment, Peru. (April 2017) - Haburaj, Vincent; Berking, Jonas; Beresford-Jones, David; Knitter, Daniel; Zeki, Leanne; Sturt, Fraser; Pullen, Alexander; Huaman, Oliver; Lane, Kevin; French, Charles
Abstract: Within arid regions allochthonous rivers as a main source of fresh water play a significant role in the spatial organisation of human occupation. This study aims at a comprehensive view on changes in the prehistoric occupation patterns within the Río Ica catchment on the southern coast of Peru. Results of different research projects are integrated. The heterogeneous character of the catchment allows us to define three sub-sections which differ greatly in terms of vegetation, relief and water regime. Based on quantitative geo-statistical methods we analyse spatio-temporal changes in human occupation from the Early Horizon (c. 1000–200 BC) through to the Inca Late Horizon (AD 1450–1532) in the context of environmental conditions, as well as socio-economic processes. Examining known archaeological sites we are able to assess the significance of environmental location factors for pre-Hispanic settlements. In addition, areas of high human interaction are identified on the basis of a classification of archaeological sites according to their function (craft/industry, cult, cooperation and trade). We thereby transfer the concept of central place theory to the spatial distribution of archaeological remains, introducing a novel approach to identifying central functions in a spatially explicit way. Our results crystallise the changing character of occupation in the study area over more than two millennia. They contribute to the ongoing debate on the decline of the Nasca culture, endorsing a complex combination of natural and socio-economic reasons. Furthermore, the results support the concept of a more widespread exchange and cooperation during 'Horizon' periods in the study area and likewise indicate that the disappearance of a supra-regional administrative polity during 'Intermediate' periods might have led to higher human activity in smaller scale societies, as reflected in a more diverse spatial organisation in terms of geomorphometric units and central areas. Highlights: Quantitative examination of pre-Hispanic occupation across the Río Ica catchment An integrative approach to analyse environmental and cultural factors The manifestation of Horizons and Intermediate Periods and how they can be measured The information potential of survey data combined with other geodata